Taxonomic status of the skull A.l.444-2 from the Pliocene of Hadar, Ethiopia - Ferguson, Walter W (Bernard Price Institute for Palaeontological Research, 1999)
A nearly complete hominid skull, A.L.444-2, from the Pliocene of Hadar in Ethiopia, has been attributed to Australopithecus afarensis Johanson, White & Coppens 1978. Comparative morphological analysis indicates that it may not conform to this species. Cranial and dental morphology and measurements of A.L.444-2 agree more closely with those of A. africanus Dart 1925, to which it could be reassigned.
Keywords: Australopithecus afarensis; Australopithecus africanus; Hadar